TO STUDY THE PSYCHIATRIC MANIFESTATIONS IN PATIENTS WITH CHRONIC KIDNEY DISEASES (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Chronic kidney disease (CKD) is a progressive multisystem disorder associated with substantial physical, psychological, and social burden. Psychiatric manifestations such as depression, anxiety, sleep disturbances, and cognitive impairment are common but often under-recognized, particularly in resource-limited settings. This study aimed to assess the prevalence and pattern of psychiatric manifestations among patients with CKD attending a tertiary care center in Central India.Methods: This prospective observational study was conducted in the Departments of General Medicine and Psychiatry at L.N. Medical College & Research Centre and J.K. Hospital, Bhopal. A total of 219 adult patients with diagnosed CKD were enrolled. Patients with a prior psychiatric illness were excluded. Psychiatric assessment was performed using the Hamilton Depression Rating Scale (HDRS), Beck Anxiety Inventory (BAI), and Brief Psychiatric Rating Scale (BPRS). Associations between psychiatric manifestations, CKD stage, dialysis status, and sociodemographic variables were analyzed.Results: Psychiatric manifestations were identified in 64.8% of patients. Insomnia/sleep disturbance was the most common manifestation (53.9%), followed by depression (49.3%), anxiety (39.3%), cognitive dysfunction (12.8%), and psychotic symptoms (6.8%). Depression prevalence increased significantly with advancing CKD stage, rising from 30% in early-stage disease to 59.3% in Stage 5 CKD. Patients undergoing maintenance hemodialysis had significantly higher rates of depression (55.1% vs. 41.3%, p=0.041), anxiety (44.9% vs. 31.5%, p=0.035), and insomnia (59.1% vs. 46.7%, p=0.029) compared with predialysis patients. Female gender, lower educational status, unemployment, and lower socioeconomic status were significantly associated with depression. Psychiatric symptom severity demonstrated a negative correlation with estimated glomerular filtration rate (eGFR).Conclusions: Psychiatric manifestations are highly prevalent among CKD patients and are associated with disease severity and dialysis dependence. Routine psychiatric screening and integrated multidisciplinary care should be incorporated into CKD management to improve quality of life, treatment adherence, and overall clinical outcomes.